Factors affecting the job preference of UP Visayas social science graduates. - Raymundo, Norma Ruth Delgado (2010.)
The issues of unemployment and job mismatch are areas concern for various state colleges and universities. Knowing the job preferene of the graduates is an indispensable tool to assist in solving these highly important issues. It is therefore important to determine the factors which influence their job preference., This paper examined the factors which affect the job preference of the graduates of Academic Year 2007-2008 and 2008-2009 of the Division of Social Sciences, College of Arts and Sciences, UP Visayas, Miagao, ILoilo. Sixty graduates participated in the study, 30 of whom accepted their first job opportunity while the other half rejected their first job opportunity. Questionnaires were used to gather data sent through e-mail. The factors considered in the study include the following: opportunity for advancement, degree-relation, social relevane, wage, security of tenure, non-wage bnefits and annual family income. The results of the study using Logistic Regression Analysis showed that opportunity for advancement degree-relation and social relevance were the significant factors affecting the job preference of the graduates at 5 percent level of significance.
Thesis (Undergraduate, Bachelor of Science in Economics) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: UP Visayas Social Sciences Graduates -- Miagao, Iloilo